Kissing Gastric Ulcers Causing Acute Pancreatitis and Portal Biliopathy: What’s the Link? - Mensier, Alexandre; Bounoua, Farid; Beretvas, Gabriel; Mosoi, Andreia; Dardenne, Sabrina (JOP. Journal of the Pancreas, 2013)
Context Acute pancreatitis is often caused by acute alcoholic intoxication or biliary stone migration. Other etiologies are less frequent. Case report We report an exceptional case of kissing ulcer as the cause of an acute pancreatitis due to the perforation of the posterior ulcus into the pancreas. More remarkable is the association of a left portal branch thrombosis and a portal biliopathy. Conclusion We describe a case of acute pancreatitis of unusual origin, associated with an equally uncommon pathology which is portal cavernoma. A literature review is then exposed to try to ascertain if there is a connection between these two entities. Image: MRI showing portal cavernoma.